Media Pendidikan Islam Berbasis Teknologi Informasi - Dede Misbahul Alam; Ahmad Faiz; Syamsir Usman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of information technology (IT) in the digital era has brought significant changes to the educational landscape, including the teaching and learning of Islamic Religious Education (IRE). This research aims to examine the forms, utilization, and impacts of IT-based Islamic educational media in supporting IRE learning. This study employs a qualitative descriptive approach through a literature review of relevant sources discussing interactive multimedia, instructional videos and animations, e-learning platforms, artificial intelligence (AI), and social media within the context of Islamic education. The findings indicate that the integration of IT-based media enhances the effectiveness of IRE learning by providing more interactive, contextual, and learner-centered instructional experiences that align with the characteristics of digital-native students. Interactive multimedia and instructional videos facilitate the visualization of abstract religious concepts, while e-learning platforms and AI support flexible, adaptive, and efficient learning processes. In addition, social media plays a significant role in expanding access to Islamic learning and digital da’wah. However, the use of information technology also poses potential negative impacts on students’ character development and lifestyle if not accompanied by adequate supervision and digital literacy. Therefore, the utilization of information technology in Islamic education must be guided wisely to not only improve instructional quality but also strengthen Islamic values and character formation.